The Meaning of The Martin Luther’s Five Soli for Christian Life Today - Pujiastuti Liza Sindoro (Sekolah Tinggi Teologi Baptis, Jakarta, 2022)
One important and influential part in the teachings of Martin Luther is the five soli teaching formula. The five soli teaching formula became the core of Martin Luther's teachings in reforming and changing the face of the church. These teachings entered into the practice of the life of the church and God's people as well as the academic study of theology. The purpose of this paper is to find out the meaning of Marthi Luther's five soli teaching formula and how it is applied to Christian life today. The method used in this paper is a descriptive analysis of related literature sources. The result of this paper is that the five Soli teachings are Luther's biographical theology, because they are formulated from life experiences, so that they can be applied to confessional theology, Seelsorge or pastoral counseling, as well as good deeds and the spirit of Protestantism.